Development and Validation of a New Short-Form Health Literacy Instrument (HLS-SF12) for the General Public in Six Asian Countries - Tuyen V. Duong; Altyn Aringazina; Gaukhar Kayupova; Thuc V. Pham; Khue M. Pham; Tien Q. Truong; Kien T. Nguyen; Win Myint Oo; Tin Tin Su; Hazreen Abdul Majid; Kristine Sørensen; I-Feng Lin; et al. (SLACK Incorporated, 2019)
Background: No comprehensive short-form health literacy (HL) survey tool has been available for general use across Asia. Objective: This study aimed to develop and validate a short-form HL instrument derived from the 47-item European Health Literacy Questionnaire (HLS-EU-Q47). Methods: A population survey (N = 10,024) was conducted from 2013 to 2015 using the HLS-EU-Q47 in 1,029 participants from Indonesia, 1,845 from Kazakhstan, 462 from Malaysia, 1,600 from Myanmar, 3,015 from Taiwan, and 2,073 from Vietnam. Validation of the short form was evaluated by principle component analysis, internal consistency, Pearson correlation, and regression analysis. Key Results: Based on responses from six countries, a 12-item short-form HL questionnaire (HLS-SF12) was developed, retaining the conceptual framework of the HLS-EU-Q47 and accounting for the high variance of the full-form (i.e., 90% in Indonesia, 91% in Myanmar, 93% in Malaysia, 94% in Taiwan, and 95% in both Kazakhstan and Vietnam). The HLS-SF12 was demonstrated to have adequate psychometric properties, including high reliability (Cronbach's alpha = .85), good criterion-related validity, a moderate and high level of item-scale convergent validity, no floor or ceiling effect, and good model-data-fit throughout the populations in these countries. Conclusions: The HLS-SF12 was shown to be a valid and reliable tool for HL surveys in the general public in six Asian countries.